2016
DOI: 10.1111/ggi.12881
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life of older Asian patients with multimorbidity in primary care in a developed nation

Abstract: Multimorbidity is associated with poorer HRQoL amongst older adults in Singapore. Review of chronic musculoskeletal pain and functional disabilities should be integrated into the comprehensive assessment of older adults in an enhanced model of primary care to improve the HRQoL of these older patients. Geriatr Gerontol Int 2017; 17: 1429-1437.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 20 publications
2
49
0
10
Order By: Relevance
“…The study also found that health-related quality of life (HRQoL) among those with multimorbidity was found to be significantly lower as compared to those without chronic conditions [18]. A study among older adults attending primary care clinics in Singapore similarly found that the most commonly reported chronic conditions were hypertension, hyperlipidemia, and diabetes, and multimorbidity was associated with lower HRQoL using the EQ-5D [19].…”
Section: Introductionmentioning
confidence: 94%
“…The study also found that health-related quality of life (HRQoL) among those with multimorbidity was found to be significantly lower as compared to those without chronic conditions [18]. A study among older adults attending primary care clinics in Singapore similarly found that the most commonly reported chronic conditions were hypertension, hyperlipidemia, and diabetes, and multimorbidity was associated with lower HRQoL using the EQ-5D [19].…”
Section: Introductionmentioning
confidence: 94%
“…The cumulative effects of multiple chronic conditions on an individual are complex; specific combinations of conditions may have greater effects on functional status, quality of life (QoL), and mortality than others [ 9 , 10 ]. Several studies have shown that multimorbidity is significantly associated with poor HRQoL in adult patients [ 11 13 ]. However, little is known about multimorbid patients’ self-perceived HRQoL in comparison with the general population and in different multimorbid patient age groups.…”
Section: Introductionmentioning
confidence: 99%
“…2 Thus, we used a list of 14 chronic conditions to de ne multimorbidity: diabetes mellitus, hypertension, lipid disorder, neurological conditions, respiratory diseases, psychiatric conditions, cancer, chronic kidney disease, heart diseases, arthritis, back/neck problems, gastrointestinal diseases, thyroid disease and physical disability. This list was previously used by Quah et al 16 to measure multimorbidity in elderly patients at a primary healthcare setting and was derived from the Singapore Mental Health Study. 30 Participants were asked to report if they had any of the chronic conditions listed above, as told to them by a registered physician.…”
Section: De Nition Of Multimorbiditymentioning
confidence: 99%